2023
DOI: 10.1021/acsnano.2c08499
|View full text |Cite
|
Sign up to set email alerts
|

An NIR-Driven Upconversion/C3N4/CoP Photocatalyst for Efficient Hydrogen Production by Inhibiting Electron–Hole Pair Recombination for Alzheimer’s Disease Therapy

Abstract: Redox imbalance and abnormal amyloid protein (Aβ) buildup are key factors in the etiology of Alzheimer's disease (AD). As an antioxidant, the hydrogen molecule (H 2 ) has the potential to cure AD by specifically scavenging highly harmful reactive oxygen species (ROS) such as • OH. However, due to the low solubility of H 2 (1.6 ppm), the traditional H 2 administration pathway cannot easily achieve long-term and effective accumulation of H 2 in the foci. Therefore, how to achieve the continuous release of H 2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…15e). 154 Among them, g-C 3 N 4 enabled sustainable photocatalytic hydrogen production in deep tissues with the help of CoP, resulting in a substantial increase in catalytic efficiency. The multifunctional nanocomposite was confirmed to have strong anti-oxidative stress and Aβ inhibition abilities; while being able to play a role in improving memory impairment and reducing neuroinflammation in AD mice.…”
Section: Application Of G-c3n4mentioning
confidence: 99%
“…15e). 154 Among them, g-C 3 N 4 enabled sustainable photocatalytic hydrogen production in deep tissues with the help of CoP, resulting in a substantial increase in catalytic efficiency. The multifunctional nanocomposite was confirmed to have strong anti-oxidative stress and Aβ inhibition abilities; while being able to play a role in improving memory impairment and reducing neuroinflammation in AD mice.…”
Section: Application Of G-c3n4mentioning
confidence: 99%
“…[116] The upconversion photocatalyst nanomaterials, UCNP@CoP@gC 3 N 4 (Table 1), improves the low solubility of H 2 (1.6 ppm) via traditional administration method and achieve the continuous release of H 2 in situ to restrain ROS in response to NIR. [117] In the subsequent discussion, we will present notable research on low-dimensional nanomaterials listed in Table 1 that exhibit dual capabilities: facile crossing of the BBB and remarkable inhibition of A𝛽, p-Tau, or ROS aggregation in AD treatment. This overview aims to offer alternative concepts and approaches for the development of multifunctional low-dimensional nanomaterials in the field of AD treatment.…”
Section: Low-dimensional Nanomaterialsmentioning
confidence: 99%
“…Yb 3+ /Er 3+ -based upconverting nanoparticles (UCNPs) can effectively convert low-energy near-infrared (NIR) light into high-energy ultraviolet (UV) or visible light through anti-Stokes emission. [24][25][26] Furthermore, previous studies have demonstrated that growing active photocatalysts on UCNPs can enhance their dispersion for photocatalytic reactions. 27,28 Therefore, incorporating both NIRabsorbing UCNPs and photocatalysts not only enhances overall light harvesting efficiency but also improves the dispersion of active sites in photocatalytic applications.…”
Section: Introductionmentioning
confidence: 99%